Subjective and physiological responses towards daylit spaces with contemporary façade patterns in virtual reality: Influence of sky type, space function, and latitude. (August 2022) - Chamilothori, K.; Wienold, J.; Moscoso, C.; Matusiak, B.; Andersen, M.
Abstract: Recent studies have shown that the façade and light patterns in a space are an important factor in the occupants' experience, but little is known about the generalizability of these findings in different lighting conditions, uses of space, or latitudes. This study employed virtual reality to investigate the effects of façade geometry and daylight patterns on space impressions and physiological responses (skin conductance, heart rate, and heart rate variability), while simultaneously examining the effect of sky type, spatial context, and latitude on participant responses. In an experimental study conducted in Switzerland and Greece, 256 participants were exposed to immersive interior scenes with six façade geometry variations with the same perforation ratio, derived from contemporary architecture. Participants evaluated the scenes under different sky types (clear sky with high or low sun angle, or overcast sky) and spatial contexts (working or socializing). The façade geometry influenced both the appraisal (how pleasant, interesting, exciting, or calming the space was perceived) and the visual appearance of the space (how complex, bright, or spacious the space was perceived). Façade geometry also influenced the reported satisfaction with the amount of view, with a façade variation with small, irregularly distributed openings driving this effect. Neither the sky type nor the spatial context influenced space impressions. Results showed a significant effect of country and an interaction between country and façade geometry only for ratings of excitement, with participants in Greece rating specific façade variations as more exciting than participants in Switzerland. Skin conductance level (logΔSCL) decreased under exposure to a social context in clear sky with a low sun angle compared to a working context in overcast sky conditions. No significant effects were found for the other physiological measures. The results of the present study show that façade geometry was the main driver of the participants' spatial experience, inducing perceptual effects that were robust to variations in sky type and space function and to regional differences (except for excitement). These findings have implications for the built environment, delineating the façade geometry as an important design tool with a high application potential across lighting conditions and space uses, and across latitudes between central and southern Europe. Highlights: The façade geometry influenced the participants' impressions of a daylit scene in VR. Neither the sky type nor the context (use of space) influenced participants' impressions. Participants in Greece rated scenes as more exciting than participants in Switzerland. Specific façade variations were rated as more exciting in Greece than in Switzerland. A significant interaction between sky type and context was found for skin conductance.